Respuesta :
2p=7q
6p-3q=24
2p-q=8
q=2p-8
substitute q=2p-8 into 2p=7q
2p=7(2p-8)
2p=14p-56
14p-2p=56
12p=56
p=4.66666666....
q=2p-8
q=2(4.6666...)-8
q=1.333333333....
Therefore, p=4.67(3.s.f) and q=1.33(3.s.f.)
6p-3q=24
2p-q=8
q=2p-8
substitute q=2p-8 into 2p=7q
2p=7(2p-8)
2p=14p-56
14p-2p=56
12p=56
p=4.66666666....
q=2p-8
q=2(4.6666...)-8
q=1.333333333....
Therefore, p=4.67(3.s.f) and q=1.33(3.s.f.)
2p = 7q
6p - 3q = 24
From 2p = 7q
p = 7q/2 substitute this in second equation.
6p - 3q = 24
6*(7q/2) - 3q = 24
21q - 3q = 24
18q = 24
q = 24/18 = 4/3
Recall, p = 7q/2 p = 7*(4/3)/2 = 14/3
Therefore, p = 14/3, q = 4/3
6p - 3q = 24
From 2p = 7q
p = 7q/2 substitute this in second equation.
6p - 3q = 24
6*(7q/2) - 3q = 24
21q - 3q = 24
18q = 24
q = 24/18 = 4/3
Recall, p = 7q/2 p = 7*(4/3)/2 = 14/3
Therefore, p = 14/3, q = 4/3